2013
DOI: 10.1007/s00246-013-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitor Nephrotoxicity in Neonates with Cardiac Disease

Abstract: Angiotensin-converting enzyme inhibitors (ACEi) are commonly used for pediatric cardiology patients. However, studies examining their safety for neonates with cardiac disease are scarce. The current study aimed to test the hypothesis that ACEi-mediated nephrotoxicity occurs in neonates and may be underappreciated in this population. A retrospective review of 243 neonates with cardiac disease between 2007 and 2010 was performed. Demographic data, weight, length, captopril and enalapril dosing, serum [K⁺], serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…They found that treatment with the ACE inhibitors enalapril and captopril significantly lowered creatinine clearance and caused renal failure in 55% of premature neonates [47]. These findings are supported by case reports examining premature infants with heart disease treated with these drugs [48].…”
Section: Ace Inhibitorssupporting
confidence: 72%
See 1 more Smart Citation
“…They found that treatment with the ACE inhibitors enalapril and captopril significantly lowered creatinine clearance and caused renal failure in 55% of premature neonates [47]. These findings are supported by case reports examining premature infants with heart disease treated with these drugs [48].…”
Section: Ace Inhibitorssupporting
confidence: 72%
“…Lindle et al [47] conducted a retrospective review of 243 neonates with cardiac disease; 38 of these neonates were born prematurely. They found that treatment with the ACE inhibitors enalapril and captopril significantly lowered creatinine clearance and caused renal failure in 55% of premature neonates [47].…”
Section: Ace Inhibitorsmentioning
confidence: 99%
“…Cohort studies have reported AKI due to nephrotoxic medications [20,69,[81][82][83][84], cardiac surgery/bypass [19,85], and sepsis [56,86], or AKI after admission to an ICU [7,20,[87][88][89].…”
Section: Aki In Critically Ill Childrenmentioning
confidence: 98%
“…Thus, it is affected by ACE inhibitors' use that may account for the high risk of renal dysfunction development in infants [19,20]. Renal failure usually occurs within few days after starting the ACE-inhibitor or after increasing its dose and usually resolves uneventfully after dose reduction or cessation of the drug [21]. …”
Section: Discussionmentioning
confidence: 99%